Pengaruh subtitusi tepung Indigofera zollingeriana dalam ransum terhadap performa broiler - Cantika Sari; Syifa Nurjannah; Nilawati Widjaya (Composite : Jurnal Ilmu Pertanian, 2022)
The purpose of this research was to influence of substistution flour Indigofera zollingeriana in Rations on performance broiler and to know the percent of the substistration of Indigofera zollingeriana flour that is able to improve performance in the most optimal broiler. This research was conducted in Cihaliwung, RT 01 RW 10, Kertamulya Village, Padalarang District, West Bandung District during 42 days start from January 27 until March 08, 2021. The method used in this research was experimental method with using Complete Randomized Design (CRD), five treatments namely R0 (commercial ration 100%), R1 (commercial ration 90% + 10% Indigofera zollingeriana flour), R2 (commercial ration 85% +15% Indigofera zollingeriana flour), R3 (commercial ration 80% + 20% Indigofera zollingeriana flour), R4 (commercial ration 75% + 25% Indigofera zollingeriana flour) with four replication, each replication consisted of five broilers. The observed changes are ration consumption, daily weight gain, and ration conversion. The collected data was analyzed by ANOVA and Duncan's test. Based on the results and discussion, it can be concluded that the substitution of flour Indigofera zollingeriana until 25% in the ration had no significant effect on ration consumption, daily body weight gain and ration conversion.